Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-51256-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial connectivity pattern of expanding gilthead seabream populations and its interactions with aquaculture sites: a combined population genetic and physical modelling approach

Abstract: In gilthead seabream the number of domesticated individuals increased annually, and escape events occur regularly in the Adriatic Sea. Still there is a lack of population genetic characteristics and evidence of the extent and geographic scale of interbreeding resulting from fish-farm escapees. We screened 1586 individuals using a panel of 21 neutral microsatellite loci in several consecutive years and here report on the medium-scale detection of hybrid and farmed seabream in the natural environment. Wild adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 86 publications
(113 reference statements)
2
18
1
Order By: Relevance
“…Recent studies have shown that scale shape can be used as a good discriminator between congeneric species [27], sympatric phenotypes [28], populations [29] or geographic variants [30]. Here, we explored morphological and microchemistry patterns of gilthead seabream scales from different population origins, i.e., wild, wild farm-associated and farmed, sampled over a relatively small spatial scale that were previously characterized genetically and morphologically (whole-body shape) [6,8]. Based on the results presented above, multiple lines of inference are reported herein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have shown that scale shape can be used as a good discriminator between congeneric species [27], sympatric phenotypes [28], populations [29] or geographic variants [30]. Here, we explored morphological and microchemistry patterns of gilthead seabream scales from different population origins, i.e., wild, wild farm-associated and farmed, sampled over a relatively small spatial scale that were previously characterized genetically and morphologically (whole-body shape) [6,8]. Based on the results presented above, multiple lines of inference are reported herein.…”
Section: Discussionmentioning
confidence: 99%
“…The gilthead sea bream, Sparus aurata, is an important demersal species in the aquaculture and fisheries sector throughout the Mediterranean. In recent years, increased numbers of wild gilthead seabream have been observed in the Adriatic Sea, and it has been suggested that rapid expansion of sea-cage farming, with the escape of fish from sea-cages and the positive effect of ocean warming on larval survival, have contributed to population increases for this subtropical species [5,6]. Several recent studies have confirmed that Adriatic tuna farms are areas of permanent residency of highly abundant wild seabream [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of the natural genetic structuring along sea bream distribution range did not provide a consistent scenario, and while some surveys report an absence of genetic differentiation among basins [18], others reported subtle genetic structure or population subdivision even at small geographical scale [19][20][21][22]; also, it cannot be excluded that aquaculture practices, also those involving other species (e.g. tunas or shellfish) have an effect in shaping the population genetic structure of the species [23]. Anyhow, these studies were mainly based on markers (e.g.…”
Section: Introductionmentioning
confidence: 92%